Evaluasi Perkerasan Lentur Menggunakan Metode Bina Marga 2017 dan AASHTO 1993 pada Jalan Denggung – Wonorejo, Sleman - Ottu, Martho; Ircham; Veronica Diana A. (ReTII, 2023)
Denggung–Wonorejo Road Section, one of the arterial roads in Yogyakarta. The road is a traffic lane with a relatively high volume of vehicles. Based on this, the structural evaluation of flexible pavement was carried out and compared the thickness of the pavement, using two methods, namely the 2017 Road Pavement Design Manual and 1993 AASHTO as comparison order to find out the parameters that cause differences in calculation results in two methods. Researchers used secondary data from Bina Marga, Yogyakarta. From these data, the calculation pavement thickness plan was carried out using the 2017 Road Pavement Design Manual and AASHTO 1993 methods. Furthermore, control was carried out using the KENPAVE program to determine forces that occur such as stresses, strains, and deflections. Pavement thickness Road Pavement Design Manual method, 2017 obtained AC – WC 4 cm, AC – BC 6 cm. CTB 15 cm, LPA Class A 15 cm. AASHTO 1993 method obtained AC – WC 5 cm, AC – BC 6 cm. Laston MS 744 25 cm, LPA Class A 4 cm. KENPAVE results in stress and strain values ​​analyzed using the KENPAVE program were 0.03910 at a depth of 21.4997 cm (below the surface layer). At a depth of 52.5030 cm, the stress and strain values ​​that cause damage in the form of rutting are 0.03998 and permanent deformation damage is 0.03698.